New model of maritime law enforcement for the empowerment of Indonesian marine agent security - Irma Rachmawati Maruf; Kamarulnizam Abdullah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Law enforcement is very crucial for Indonesian safety in sea maritime. In many countries, the agency enforces maritime law. Mostly of legal international trade moves by seas and is illegally used by smugglers transporting prohibited substances or illegal migrant workers.   Ships are also vulnerable to violence. Ships are robbed or hijacked, raising concerns that such attacks could finance terrorism or result in seized vessels being used as floating bombs to attack essential ports. The Indonesian Government may also have a strategic policy to prevent such illegal carriage by sea. It must have harmonies of the regulations state competing interest in exploiting and regulating maritime activities. This article will seek agencies to implement law, security, and safety at sea and review marine agencies. The agents are expected to avoid law enforcement in the sea, which is currently ineffective, causing competition between authority institutions or interests, all of which are detrimental to implementing the rule of law itself. In Indonesian shipping law, law enforcement of marine law is not only be handled by one department. Some regulations give different authority to any department to force the direction. So, there is no integration system to move the marine law if the law separates the sectoral approach that caused many law problems; one of them is an overlap in authority which tends to be a conflict of interest among them. Law enforcement at sea has particular characteristics and extraordinary scopes under the applicable legal regime in the sea area